ARE DOMESTIC FIRMS EXPOSED TO SIMILAR CURRENCY RISK AS INTERNATIONAL TRADING FIRMS? (International Journal of Banking and Finance, 2022)
This paper reports key findings about currency risk using two samples of listed firms: one sample with zero foreign currency revenues, hence having zero-currency risk; and the other sample with positive revenues in foreign currencies from foreign transactions. The latter is therefore, exposed to currency risk. Asset pricing theories predict that stocks of currency-risk-exposed firms should suffer significant currency risk, while those firms with zero-currency-risk should not have any effect from currency risk since currency transactions across borders is nil. The latter hypothesis has yet to be tested explicitly, so there is a gap in the literature. We report stock returns are significantly affected not just for firms with foreign-currency revenues but also for firms with zero foreign-currency transactions. These findings are useful to top management of all businesses to undertake currency-hedge plans for both domestic and international trading firms.